Visual development in infants with prenatal post-haemorrhagic ventricular dilatation. Issue 4 (1st December 2006) - Ricci, Daniela; Luciano, Rita; Baranello, Giovanni; Veredice, Chiara; Cesarini, Laura; Bianco, Flaviana; Pane, Marika; Gallini, Francesca; Vasco, Gessica; Savarese, Immacolata; Zuppa, Antonio A; Masini, Lucia; et al.
Abstract : Objective: The aim of this study was to assess visual function in 13 infants with evidence of prenatal post haemorrhagic ventricular dilatation. Design: Infants were assessed at 5, 12 and 24 months using a battery of tests specifically designed to assess various aspects of visual function in infancy. Visual findings were correlated with several variables, including extent of the lesion and presence of epilepsy. Results and conclusions: Abnormalities of visual function were frequent (over 60%) in our cohort at age 2 years, ranging from isolated abnormal ocular movements to severe abnormalities of all the aspects of visual function assessed. The most severe and persistent abnormalities of visual function were found in infants with grade IV intraventricular haemorrhage and shunted hydrocephalus who also had epilepsy in the first year.